Evaluation of sowing time and seed treatment fungicides on Microdochium spp. DNA quantity in winter wheat cultivars - Sabeckis, Aurimas; Semaškienė, Roma; Jonavičienė, Akvilė; Lavrukaitė, Karolina; Venslovas, Eimantas (Frontiers in Plant Science, 2025)
Root rots, seedling blights and snow mold diseases caused by Microdochium nivale and M. majus threaten winter wheat production in temperate regions. This study investigated the occurrence and dynamics of both pathogens in three-year field trials using quantitative PCR analysis of winter wheat cultivars sown at different times and treated with various seed treatment fungicides. Both species were consistently detected, but their prevalence varied by year: M. nivale was dominant under prolonged snow cover in 2023, whereas M. majus reached highest levels in 2022, when snow cover was less persistent. Later sowing generally reduced M. nivale infection in years with moderate disease pressure, although this effect was diminished under epidemic conditions. Seed treatment fungicides containing fludioxonil or succinate dehydrogenase inhibitor compounds (fluxapyroxad and sedaxane) consistently suppressed pathogen DNA levels, whereas triazole-dominant treatments showed more variable results. Cultivar-related differences were also evident, with ‘Ada’ and ‘KWS Emil’ frequently exhibiting higher infection levels than ‘Skagen’ or ‘Patras.’ These findings highlight that Microdochium spp. incidence is shaped by the interaction of environmental conditions, agronomic practices, and host genotype. By integrating these factors, this study advances our understanding of pathogen ecology and contributes to sustainable management strategies for winter wheat under changing climatic conditions.